(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article considers new words, namely neologisms, that appear in the language and the ways of their formation in the language. In addition, the pragmatic features of neologisms in Uzbek and English languages are discussed with the use of examples.